Comparative effectiveness and harms of intravitreal antivascular endothelial growth factor agents for three retinal conditions: a systematic review and meta-analysis. Issue 4 (8th November 2018) - Low, Allison; Faridi, Ambar; Bhavsar, Kavita V; Cockerham, Glenn C; Freeman, Michele; Fu, Rochelle; Paynter, Robin; Kondo, Karli; Kansagara, Devan
Abstract : Intravitreal antivascular endothelial growth factor (VEGF) agents are widely used to treat ocular conditions but the benefits and harms of these treatments are uncertain. We conducted a systematic review to compare the effects of aflibercept, bevacizumab and ranibizumab on best-corrected visual acuity (BCVA) changes, quality of life and ocular or systemic adverse events in patients with neovascular age-related macular degeneration (NVAMD), diabetic macular oedema (DME) and central or branch retinal vein occlusion (RVO). We searched published and unpublished literature sources to February 2017 for randomised controlled trials and cohort or modelling studies reporting comparative costs in the USA. Two reviewers extracted data and graded the strength of the evidence using established methods. Of 17 included trials, none reported a clinically important difference (≥ 5 letters) in visual acuity gains between agents. Nine trials provide high-strength evidence of no difference between bevacizumab and ranibizumab for NVAMD. Three trials provide moderate-strength evidence of no difference between bevacizumab and ranibizumab for DME. There was low-strength evidence of similar effects between aflibercept and ranibizumab for NVAMD, aflibercept and bevacizumab for RVO and all three agents for DME. There was insufficient evidence to compare bevacizumab and ranibizumab for RVO. Rates of ocular adverse events were low, and systemic harms were generally similar between groups, although 1 DME trial reported more arterial thrombotic events with ranibizumab versus aflibercept. Overall, no agent had a clear advantage over another for effectiveness or safety. Aflibercept and ranibizumab were significantly less cost-effective than repackaged bevacizumab in two trials. Systematic review registration number: CRD42016034076.